PENGEMBANGAN E-MODUL DENGAN MENGGUNAKAN DISCOVERY LEARNING BERBANTUAN APLIKASI WORDWALL UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Mhd Azmi Azwar; Jihan Hidayah Putri; Nur Rahmi Rizqi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
With the help of the Wordwall application and discovery learning, this project intends to create an e-module that will enhance students' comprehension of mathematical concepts related to circles. The validation results showed that the media experts received an average score of 4.64 in the valid category, the LKPD experts received an average score of 4.33 in the valid category, and the teaching module experts received an average score of 4.3 in the valid category. The evaluation of teacher responses to the e-module created during the trial is used to review the practicality analysis. Specifically, small-scale trials received an average score of 70.9% in the very practical category, while field-scale trials received an average score of 89.6%, placing them in the very practical category. Student responses on a small scale received an average score of 78.40% in the practical category, and field trials received an average score of 81.46% in the very practical category.The average post-test score for students' grasp of mathematical concepts in small-scale trials using discovery learning was 70.5, placing them in the effective category. On the field scale, the average post-test score was 83.8%, placing them in the very effective category, indicating a rise between small-scale and field trials.